Systems thinking skills included in the mathematics textbook for the third intermediate grade - et. al., Nour Mahmoud Abdul Reda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Abstract: The aim of the current research is to find out the extent to which systems thinking skills are included in the mathematics textbook scheduled for the third intermediate grade for the academic year (2020-2021) by answering the main research question: What are the systems thinking skills included in the mathematics textbook for middle third grade? The analytical descriptive approach was used, and to achieve the goal of the research, a list of the main systemic thinking skills and sub-skills was prepared, and after analyzing the content of the mathematics textbook, the reliability of the analysis was verified through the analysis over time and through others, and it obtained a reliability rate of 98% using the Holsti equation. The researchers found that all systems thinking skills were included, but in varying proportions. The percentage of systemic relations perception skill (25%), systems analysis skill (40%), systems installation skill (17%), systems evaluation skill (18%), and in light of the results of the analysis, several recommendations and suggestions were reached.